Ajaran Tri Parartha dalam Kakawin Aji Palayon - Anak Agung Gede Wiraputra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Literary work is a life guide of the Balinese Hindu community that still exists until today. One type of traditional Balinese literary work that is rich in moral teachings, especially related to Tri Parartha is kakawin Aji Palayon. This paper seeks to uncover the teachings of Tri Parartha contained in Aji Palayon's kakawin literary work with a set of semiotic and religious theories supported by content analysis and descriptive analysis methods. The results of the analysis show that Kakawin Aji Palayon is a traditional Balinese literary work in the form of a song that tells about the journey of the atman since leaving the rough body until it reaches shunya laya (a place of eternal peace). On the journey the atman is also filled with the teachings of Tri Parartha, namely asih (compassion), punia (sacrifice / sincere gift), and bhakti (truth devotion) which is dominantly found in chapter 1, 3, and 6. With high wisdom and understand the teachings of Tri Parartha well, then the atman can pass through various kinds of obstacles and temptations, so that finally he reaches shunya laya (place of eternal peace).